INVESTIGATION OF ALUMINUM TOXICITY AMONG WORKERS IN ALUMINUM INDUSTRY SECTOR - Boran, Ahmad M.; Al-Khatib, Ahed J.; Alanazi, Bader S.; Massadeh, Adnan M (European Scientific Journal, ESJ, 2013)
The study was conducted to evaluate urine aluminum concentration among a total of 150 participants (80 aluminum technicians and 70 non- aluminum technicians as a control). Data were collected through a previously prepared questionnaire which consists of two parts. The first part concerned with demographic data such as age and nationality. The second part concerned with occupational data such as working hours, working years, smoking, and diseases. The mean concentration of aluminum is 51.62+ 29.59 μg/l and the mean concentration of group control 16.32 + 12.49 μg/l. The following variables were associated significantly with aluminum concentration: age, weekly working hours, smoking and daily smoking packets. According to our study, aluminum workers have high concentrations of urine aluminum compared with other studies, in addition to that the incidence of diseases in relation to exposure is low, simply because: 1-Self reported questionnaires may be not a proper way to collect data about diseases. 2- Traditional surveillance approaches used in public health practice are difficult to apply to metals poisoning because adverse health effects related to metal exposure may not be clinically diagnosed, except at very high exposure levels, and are not usually listed as reportable diseases. Finally Special safety precautions and educational programs are also needed to limit the aluminum exposure in this industrial group.